ETHNOPHARMACOLOGICAL USES OF PLANTS AMONG INHABITANTS SURROUNDING SURU AND ZANSKAR VALLEYS OF COLD DESERT, LADAKH - TSEWANG RINCHEN; SHREEKAR PANT (International Journal of Pharma and Bio Sciences, 2014)
Trans Himalaya of the Indian Himalayan region is repository of indigenous knowledge and practices. Recent re-emergence of herbal medicine along with the ever- escalating threats to biodiversity and the intensifying biopiracy controversies have necessitated an urgent need of documentation of the traditional use (s) of bioresoures. Therefore, an attempt has been made to document the ethnopharmacological uses of plants utilized in the traditional medicine system/household remedies by the inhabitants of the cold desert. We recorded a total of 68 plant species belonging to 58 genera and 34 families which are used traditionally to cure various diseases/ailments. Thirty three plant species are non-native whereas thirty five species are native to Indian Himalayan region. Various part (s) of these species are used to cure cough/cold, bronchitis, fever, liver disorders, kidney stone, joints pain etc. The study would help in developing a comprehensive data base of ethnopharmocological uses of plants, help in strengthening the health care system in the villages/rural areas and also in conserving the traditional knowledge and practices for posterity.